(untitled) (Bulletin KNOB, 2005)
In the period 1977-1984 the Royal Palace Het Loo in Apeldoorn, the Netherlands, was thoroughly restored into a museum, highlighting the late 17th-century phase in which King William III and Queen Mary II resided at Het Loo. The restoration of Het Loo was severely criticized. A walk was laid out through the approximately 40 rooms in the Palace which are open to the public. The main apartments were furnished in the style of the first main residents, the remaining rooms were devoted to the other members of the House of Oranje-Nassau, in chronological order. This implied that the rooms devoted to the last main resident, Queen Wilhelmina (1880-1962), were necessarily reconstructed in the rooms at the end of the visitors’ route, which were not intended for that purpose originally. The wainscoting was retained, but all the movable parts of the interior were transferred to the new museum rooms. In principle, all the relocated rooms could be rebuilt again in their original places, but the financial situation does not permit this. However, it is possible to change the existing furnishing of the 19th-century rooms in order to create a more authentic image. Recently the drawing room of Queen Wilhelmina was refurnished with authentic interior components from the depots of Palace Het Loo. The furnishing was realized on the basis of photographs of the drawing room dating from before the Second World War, when the rooms of the Royal Family were documented in view of the chaos to be expected upon arrival of the German occupier. A few lacking components were replaced by similar pieces from the collection. The result is perhaps not a richer but definitely a more convincing image of a Royal drawing room from before the Second World War, because of the fact that one particular residential phase was opted for.